DESIGN AND UP HEAVAL BUCKLING ANALYSIS OF ONSHORE PIPELINE IN EAST INDONESIA - Putra Paskala, Pangrango
The high level of energy demand makes oil and gas production activities continue to grow rapidly, both in offshore and onshore areas. One of the needs to support oil and gas production facilities is a distribution system. In onshore areas, this distribution system is provided by pipeline system. A company plans to build a land pipeline network consisting of gas and liquid pipes to support oil and gas distribution activities in East Indonesia. The pipeline design must meet the criteria of API 5L in material selection, ASME B31.8 and ASME B31.4 in the pipe wall thickness calculation, DNV RP E305 in determining the coating weight dimention. In addition, analyzes are carried out to ensure that the pipes can safely meet the criteria under operating conditions. The end expansion analysis is in accordance with DNV GL RP F1104 standard, pipe stress analysis using the CAESAR II program and up heaval buckling analysis based on the OTC 6335 standard. After calculating the pipe design and analysis, it is found that the gas pipe and liquid pipe consist of materials steel pipe API 5L X65 with a cladding layer of Incoloy825 type and an external anti-corrosion coating in the form of 3LPP. The selected wall thicknesses for gas and liquid pipes are 0.562 in and 0.109 in. The coating weight used in the pipe system is a cuboid installed every 12.2 m. The dimensions of the ballast for gas and liquid pipes are 1.8 m and 0.8 m. The results of the end expansion analysis show that gas pipes and liquid pipes have an expansion of 253.41 mm and 79.07 mm at each end. The pipe stress analysis conducted shows that the pipe has met the design criteria because there is no stress value that exceeds the allowable limit along the modeled pipeline. Furthermore, up-heaval buckling analysis is being conducted to determine the imperfection height of the soil so that the pipe does not buckle due to axial force. Up heaval buckling analysis shows that gas and liquid pipes will be buckled when the imperfection height values exceed 3.7 m and 1.65 m.